Mutation in the RmβAOR gene is associated with amitraz resistance in the cattle tick Rhipicephalus microplus - Corley, Sean W. (2013)
We aimed to describe the evolution of resistance to amitraz in Rhipicephalus microplus in the field and to test the association between amitraz resistance and the frequency of a mutation in the β-adrenergic octopamine receptor gene (RmβAOR). We established six populations of Rhipicephalus microplus ticks in similar paddocks by the admixture of ticks from strains known to be susceptible and resistant to amitraz and synthetic pyrethroids. Each population was managed using one of three acaricide treatment regimes: always amitraz, always spinosad, or rotation between amitraz and spinosad. We used microsatellites to elucidate population structure over time, an SNP in the para-sodium channel gene previously demonstrated to confer resistance to synthetic pyrethroids to quantify changes in resistance to synthetic pyrethroids over time, and a nonsynonymous SNP in the RmβAOR, a gene that we proposed to confer resistance to amitraz, to determine whether selection with amitraz increased the frequency of this mutation. The study showed panmixia of the two strains and that selection of ticks with amitraz increased the frequency of the RmβAOR mutation while increasing the prevalence of amitraz-resistance. We conclude that polymorphisms in the RmβAOR gene are likely to confer resistance to amitraz.